Symbolic Interactionism and Feminist Readings of Women in Igbo Folktales - Anyachebelu, Adaora Lois (NIU Journal of Humanities; Vol 10 No 4 (2025): NIU Journal of Humanities, Vol. 10 No. 4, December 2025DO - 10.58709/niujhu.v10i4.2354, 2025)
Gender discourse has assumed a prominent position in contemporary African scholarship, with many scholars attributing women’s challenges to entrenched patriarchal ideologies within African societies. In Igboland, these perspectives often highlight male dominance as the root cause of female marginalization. However, this study re-examines women’s representations in Igbo folktales to uncover other underlying factors contributing to women’s experiences beyond patriarchy. Anchored on feminist literary theory, Principle of Female Mortification and symbolic interactionism, the paper investigates how women’s portrayals in selected Igbo folktales reflect individual agency, internalized gender dynamics, and social attitudes that sometimes perpetuate female subjugation. The study adopts a qualitative research design, employing purposive sampling to select and analyze relevant folktales from written anthologies. Through critical textual and thematic analysis, the findings reveal that while patriarchal structures influence women’s conditions, certain negative experiences are also self-engendered through women’s complicity, rivalry, and moral failings as depicted in the tales. These narratives illustrate that Igbo oral tradition serves both as a mirror and a moral compass, using storytelling to instruct, critique, and reform social behavior. The study concludes that meaningful gender transformation in Igbo society requires a dual approach: confronting structural patriarchy while encouraging individual introspection, self-assessment, and moral mortification among women. It recommends renewed attention to folktales as educational tools for promoting self-awareness, mutual respect, and societal harmony. Keywords: Women, Igbo Folktales, Patriarchy, Feminist Theory, Symbolic Interactionism, Self-Mortification.